2014
DOI: 10.1155/2014/731039
|View full text |Cite
|
Sign up to set email alerts
|

RANKL Expression in Periodontal Disease: Where Does RANKL Come from?

Abstract: Periodontitis is an inflammatory disease characterized by periodontal pocket formation and alveolar bone resorption. Periodontal bone resorption is induced by osteoclasts and receptor activator of nuclear factor-κB ligand (RANKL) which is an essential and central regulator of osteoclast development and osteoclast function. Therefore, RANKL plays a critical role in periodontal bone resorption. In this review, we have summarized the sources of RANKL in periodontal disease and explored which factors may regulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 61 publications
1
77
0
14
Order By: Relevance
“…It inhibits bone or tooth resorption by strongly binding to its ligand (RANKL), hence preventing the latter from binding to its receptor (RANK) (30).…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits bone or tooth resorption by strongly binding to its ligand (RANKL), hence preventing the latter from binding to its receptor (RANK) (30).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies that reported the stimulatory effect of IL-18 on GM-CSF expression in CD4 + T cells [11][12][13] , we hypothesized that the free IL-18BP in culture supernatants derived from RANKL-treated RAW264. An increase in the level of IL-18 has been observed in the serum or pathological tissue in individuals with rheumatoid arthritis [28][29][30][31] or periodontitis 32,33) , both of which are well-recognized as inflammatory diseases with bone destruction, through RANKLinduced osteoclast formation [34][35][36] . The results in our present study may help explain how RANKL, IL-18 and IL-18BP are involved in the cell-cell interactions between osteoclast precursor cells and CD4 + T cells in these bone-destructive disorders.…”
Section: Effect Of Conditioned Medium Derived From Raw2647 Cells On mentioning
confidence: 99%
“…Possui importante papel na regulação da osteoclastogênese devido a sua ação na expressão de RANK-L (CHEN et al, 2014).…”
Section: Fator De Necrose Tumoral-α (Tnf-α)unclassified
“…O nível de RNA-m de RANKL está aumentado em processos inflamatórios como da DP. As citocinas IL-1β e TNF-α podem regular a expressão de RANKL em células periodontais e aumentar a formação de osteoclastos (CHEN et al, 2014).…”
Section: Ligante Do Receptor Ativador De Nf-kb (Rankl)unclassified
See 1 more Smart Citation